Are corporate social responsibility active firms less involved in earnings management? Empirical evidence from China - Pasko, Oleh; Chen, Fuli; Proskurina, Nelia; Mao, Rong; Gryn, Viktoriia; Pushkar, Iryna (Business: Theory and Practice, 2021)
This paper investigates whether corporate social responsibility active (CSR active) firms operate dissimilarly from other firms in their financial reporting. Specifically, we examine whether the corporate social responsibility (CSR) attitude of a firm sways its reporting incentives, in respect of the extent of earning management. To test our predictions, we use a sample of 25,861 year-company observations, corresponding to 3538 Chinese listed companies, for the period 2009–2019. We find a significant positive association between CSR activity and earning management assessed by the level of discretionary accruals in Chinese listed companies. Moreover, we document that Chinese CSR active firms engage more in earnings management through discretionary accruals than CSR inactive firms. These findings are consistent with the opportunistic financial reporting hypothesis: advances in CSR used by managers to safeguard their position by evading scrutiny from stakeholder activists. This study contributes to the growing awareness among investors, stakeholders and researchers that we should distinguish between CSR active firms and socially responsible firms and that being the latter entail something more than just mechanically produce CSR reports.